A Critical Analysis of the Most Famous Kurdish Translation of Khayyam’s Quatrains - Hassan Armkan; Fatemeh Modarresi (پژوهشنامه ادبیات کردی, 2022)
Khayyam’s quatrains have been translated into many languages ​​and have brought worldwide fame to this poet and a great honor for Iranian literature. Khayyam’s quatrains have been translated several times into Kurdish. One of the most successful translations is the translation of the famous Kurdish poet, writer and translator, Abdul Rahman Sharafkandi, nicknamed “Hejar”. While faithful to the structure and content of Khayyam’s poetry, this translation is a kind of free and conceptual translation. The translator tries to convey Khayyam’s view of the world inside and outside, his main message, and his poems’ general spirit to the Kurdish audience. He attempts to transmit the semantic and formal features of the original poem such as meter and form, tone and firmness of Khayyam’s speech, and its external and internal music in his translation. The present study critically analyzes this translation formally and semantically, adopting a descriptive-analytical method and relying on library and documentary data. It explores the translator’s method in translating Khayyam’s poetry. The results of the study indicated the following factors led to the translator’s success in his translation: the poet being a translator himself, his complete mastery of the source and target languages, his correct understanding of the content of the source text, and the intention of the original author, avoiding literal translation, choosing tone and words appropriately and recreating the internal and spiritual music of Khayyam’s poetry.